Effects of dried distillers grain with solubles on growing-finishing pig performance - Linneen, S.K.; Gottlob, R.O.; Main, R.G.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Three experiments were conducted to determine the effects of increasing dried distiller’s grains with solubles (DDGS) on growth performance and palatability in growing-finishing pigs. In Exp. 1, a total of 1,050 pigs (initially 104.9 lb) were used in a 28-d study in May 2002. Pigs were fed diets with either 0 or 15% DDGS and 0, 3, or 6% added fat, for a 2 × 3 factorial arrangement. Overall, there were no DDGS × fat content interactions (P = 0.20). There was an improvement (linear, P<0.01) in ADG and F/G with increasing added fat and no difference in growth performance between pigs fed 0 or 15% DDGS. In Exp. 2, a total of 1,038 pigs (initially 102.1 lb) were used in a 56-d study in August 2005. Pigs were fed diets with either 0, 10, 20, or 30% DDGS from the same ethanol plant as in Exp. 1. Overall (d 0 to 56), there was a trend for decreased ADG (linear, P<0.10) and ADFI (linear, P<0.06) as DDGS increased. The greatest reduction occurred in pigs fed more than 10% DDGS. In Exp. 3, a total of 120 growing pigs (initially 48.7 lb) were used in a 21-d feed preference study in October 2005. Pigs were randomly allotted to a pen with 4 feeders, each containing a separate dietary treatment. Pigs were offered diets based on corn-soybean meal, with 0, 10, 20, or 30% DDGS from the same source as in Exp. 1 and 2. For all periods (d 0 to 7, 7 to 21, and 0 to 21), there was a decrease in ADFI (quadratic, P<0.01) as DDGS increased in the diet. The most dramatic decrease was observed between 0 and 10% DDGS. Experiment 1 showed no difference in growth performance in pigs fed 0 or 15% DDGS. In Exp 2, at DDGS contents higher than 10%, there were trends for decreased ADG and ADFI; in Exp. 3, ADFI decreased with increasing DDGS in the diet. In summary, DDGS from the ethanol plant tested can be used at 10 to 15% in finishing diets without reducing pig performance. Higher percentages of DDGS in the diet decreased ADFI in growing and finishing pigs.
Keywords: Dried distillers grains; Growing-Finishing pigs; Swine